2020
DOI: 10.1097/md.0000000000018371
|View full text |Cite
|
Sign up to set email alerts
|

Coronary sequelae of Kawasaki disease treated with rotational atherectomy and drug coated balloon

Abstract: Introduction: Kawasaki disease (KD) is an acute vasculitis syndrome that mainly affects children and is the first cause of acquired heart disease. Coronary artery lesion is the most serious complication of KD. Only two previous studies have reported similar cases, but we reported patient was younger and had a longer follow-up. Patient concerns: We reported a case of coronary sequelae of KD treated with rotational atherectomy and drug coated balloon (DCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…4) However, to date, only few case reports have described the use of DCB in KD patients with short-term follow-up, mostly in middleaged patients with significant calcified lesions that required rotational atherectomy. 5,6) The present case indicated that DCB therapy may achieve promising outcomes for adolescent KD patients in the 1-year clinical and imaging follow-up, although the long-term efficacy and safety of the "leave nothing behind" strategy still need further validation.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…4) However, to date, only few case reports have described the use of DCB in KD patients with short-term follow-up, mostly in middleaged patients with significant calcified lesions that required rotational atherectomy. 5,6) The present case indicated that DCB therapy may achieve promising outcomes for adolescent KD patients in the 1-year clinical and imaging follow-up, although the long-term efficacy and safety of the "leave nothing behind" strategy still need further validation.…”
Section: Discussionmentioning
confidence: 77%
“…4) However, reports of DCB use for KD patients are still limited, especially for younger patients. 5,6) Here, we present the case of an 18-year-old female undergoing successful PCI for possible sequelae of KD with multimodality-guided DCB treatment.…”
mentioning
confidence: 99%
“…4 There are only a few case reports on use of drug-coated balloon for treating coronary sequelae of Kawasaki disease in adults, two cases were combined with rotational atherectomy by Shiraishi and Shi, respectively, another was combined with laser excimer angioplasty and cutting balloon by Kawamura. [5][6][7] They all showed good results, and rotational atherectomy followed by drug-coated balloon dilation might contribute to deferring repeat intervention. 5 To our knowledge, our case is the first to describe successful percutaneous revascularisation using drug-coated balloon for coronary sequelae of Kawasaki disease in paediatric.…”
Section: Discussionmentioning
confidence: 98%
“…Angioplasty of these lesions is often complex, whatever the technique used, and is exposed to immediate complications (coronary rupture, cardiac tamponade, death) or delayed complications (false aneurysms, restenosis or thrombosis related to under-expansion and/or malapposition). 7 Detailed evaluation of the severity of calcifications is important to adapt to the right therapeutic strategy before stenting. 6 These structural characteristic details are revealed and quantified only by using intravascular imaging.…”
Section: Discussionmentioning
confidence: 99%